Terrain induced wind profiles - Bayraktar, Evren. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
In this study, the WOCSS meteorological model was used to produce threedimensional gridded wind fields. The results simulated by WOCSS were visualized in MATLAB environment. The WOCSS model was performed using a sample data set which was supplied by Prof. Ludwig and an extracted data set from this sample by reducing the number of available data in the given data set. Then, the WOCSS model was performed on Bosphorus area. In the simulation of three-dimensional wind fields, air observation data from four surface and one upper air station were used. The surface air observation data were reported at Florya, Göztepe, Kireçburnu and Kumköy, while the radiosonde data were reported at Göztepe station. All the stations are located inside the model domain and they are spread out through the domain so to represent terrain features. WOCSS model was used to produce wind fields for the data sets belonging to 18 August, 11 October, and 10 December 1998. The model was performed on a gridded domain covering 40 km × 40 km with grid spacing 1 km. The major conclusion to be drawn is that reasonable wind analysis can be performed by using WOCSS which is a quite easy model to use and does not require large computing resources for operation. As it is always true with diagnostic models, the results may be improved by the more input wind data. However, with provided data for this study, the terrain effect on the flow was able to be simulated, and it was concluded that the dispersion or turbulence estimation models which require a threedimensional gridded wind field can use the results of WOCSS as input.
Keywords: Winds.; Meteorology.